2012
DOI: 10.1002/mats.201100088
|View full text |Cite
|
Sign up to set email alerts
|

Langevin Dynamics Simulation of Chain Crosslinking into Polymer Networks

Abstract: A Langevin dynamics simulation method is presented to create polymer networks. The properties of the network are found to depend on the interactions between segments of the precursor chains, the FJCs, and the excluded volume chains modelled by the repulsive WCA potential. The mean square displacements of the crosslinkers in both networks show scaling behaviors with chain length. The shear modulus depends on the preparation method and is in fair agreement with theory. The method allows the study of supramolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…They analyzed canonical ensemble, Hoover ensemble, and Parrinello-Rahman ensemble and showed that despite the presence of intrinsic probability gradients in this system, a Langevin dynamics approach samples the extended phase space in the correct fashion. Wu, Li and Nies [51] applied Langevin dynamics method to the problem of cross-linking into polymer networks. Commercially available software package GROMACS 4.0 was used for simulation.…”
Section: Langevin Dynamicsmentioning
confidence: 99%
“…They analyzed canonical ensemble, Hoover ensemble, and Parrinello-Rahman ensemble and showed that despite the presence of intrinsic probability gradients in this system, a Langevin dynamics approach samples the extended phase space in the correct fashion. Wu, Li and Nies [51] applied Langevin dynamics method to the problem of cross-linking into polymer networks. Commercially available software package GROMACS 4.0 was used for simulation.…”
Section: Langevin Dynamicsmentioning
confidence: 99%
“…Based upon the united-atom polyethylene force field [19], a realistic model of random polymer networks was developed with telechelic chains, whose maximal functionality of the crosslinker could be easily adjusted by the relative size of the particles [20]. The shifted Morse potential at the inter-atomic distance r, ( ) morse V r , was introduced to normal molecular dynamics simulations to govern the cross-linking of polymer chains with special end groups.…”
Section: Introductionmentioning
confidence: 99%
“…All particles had the same reactivity and the random collisions between such reactive particles lead to increasing fractions of central particles with 1-4 end group particles. Because of the short-ranged nature of the reactions, the reactive potential introduced had almost no interference to the population of other particles in the systems [20]. One of the random polymer networks formed through chain-end cross-linking with such reactive particles at both ends is shown in Figure 1b, in which the functionality of the cross-linker was also set to 4.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Based upon the united-atom polyethylene force field, 19 a realistic model of random polymer networks was developed with telechelic chains, whose maximal functionality of the cross-linker could be easily adjusted by the relative size of the particles. 20 The shifted Morse potential at the inter-atomic distance r,…”
Section: Introductionmentioning
confidence: 99%
“…Because of the short-ranged nature of the reactions, the reactive potential introduced had almost no interference to the population of other particles in the systems. 20 One of the random polymer networks formed through chain-end cross-linking with such reactive particles at both ends is shown in Figure 1B, in which the functionality of the cross-linker was also set to 4. The conversion of polymer chains into the large polymer network was efficient seeing from the fractions of end-groups or chains reacted in Table 1.…”
Section: Introductionmentioning
confidence: 99%